PROMOSI PAKET WISATA DI PT.ALOHAA MEDIA INDONESIA KOTA PADANG PROVINSI SUMATERA BARAT - Sari, Intan Ayu Ovia; Ibrahim, Mariaty (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
This research aims to determine the promotion of tour packages at PT. Alohaa Media Indonesia and the factors that influence the promotion of tour packages at PT. Alohaa Media Indonesia. In this research, researchers used qualitative research methods. Research using this qualitative method is research that intends to describe and understand phenomena about what is experienced by research subjects, for example regarding actions, behavior, perceptions, efforts, motivation and so on, to describe and explain the conditions that occur by collecting data and information in the field. The key informants in this research are the CEO of PT. Alohaa Media Indonesia, and the staff of PT. Alohaa Media Indonesia who is responsible for promotions and is also a tour guide. In this research, the data collection techniques used were interviews, observation and documentation. Based on the research results, it can be concluded that in promoting tour packages, PT. Alohaa Media Indonesia uses a promotional mix to promote its tour packages. The promotion is carried out in the form of promotion through advertising which is carried out by placing advertisements on Google Maps, social media (Instagram, Facebook and WhatsApp). Promotion through sales promotions which are carried out by providing discounts or discounts to consumers, providing free accommodation, and providing gifts and souvenirs. Promotion through public relations is carried out by participating in, organizing and sponsoring an event. Promotion through direct marketing is carried out by communicating or sending messages directly with consumers using social media and word of mouth. Promotion through individual sales which is carried out by means of sales presentations to potential consumers. Keywords: Promotion, Tour Packages, PT. Alohaa Media Indonesia